The search of proper oxygen carriers for chemical looping partial oxidation of carbon. (15th March 2017) - Zhang, Jinzhi; He, Tao; Wang, Zhiqi; Zhu, Min; Zhang, Ke; Li, Bin; Wu, Jinhu
Highlights: A method was offered in this work to distinguish the oxidation ability of OCs. Three zones were divided by three reactions in the Elliham diagram. CaFe2 O4 and Ca2 Fe2 O5 were found to be proper for chemical looping partial oxidation. Abstract: Chemical looping partial oxidation process has more advantages over conventional chemical looping process, which can not only completely avoid the problem of greenhouse gas emissions, but also supply syngas products for chemical industry. The aim of the present work is to perform fundamental investigation on chemical looping partial oxidation of solid fuels. Production of CO through chemical looping partial oxidation of carbon was investigated in order to find proper oxygen carrier with good reactivity and high selectivity. A simple and easy to use method based on the zone division of Ellingham diagram was offered to distinguish the oxidation ability of various metal oxides, and three zones including complete oxidation, partial oxidation and inert zones were divided. CaFe2 O4, Ca2 Fe2 O5 and FeAl2 O4 in partial oxidation zone together with Fe2 O3 in complete oxidation zone were chosen as target oxygen carriers (OCs) for chemical looping partial oxidation of carbon in this work. Of the target metal oxides, CaFe2 O4 and Ca2 Fe2 O5 were found to have fast reaction rate, large oxygen-carrying capacity, high CO selectivity, and good regeneration performance, which made them very attractive for the purpose of chemical looping partial oxidation of solid fuels in real applications.